A pilot study of surgical telementoring for leg fasciotomy. Issue 2 (10th October 2017) - Talbot, Max; Harvey, E J; Berry, G K; Reindl, R; Tien, H; Stinner, D J; Slobogean, G
Abstract : Introduction: Acute extremity compartment syndrome requires rapid decompression. In remote locations, distance, weather and logistics may delay the evacuation of patients with extremity trauma beyond the desired timeline for compartment release. The aim of this study was to establish the feasibility of performing telementored surgery for leg compartment release and to identify methodological issues relevant for future research. Methods: Three anaethetists and one critical care physician were recruited as operators. They were directed to perform a two-incision leg fasciotomy on a Thiel-embalmed cadaver under the guidance of a remotely located orthopaedic surgeon. The operating physician and the surgeon (mentor) were connected through software that allows for real-time supervision and the use of a virtual pointer overlaid onto the surgical field. Two experienced orthopaedic traumatologists independently assessed the adequacy of compartment decompression and the presence of iatrogenic complications. Results: 14 of 16 compartments (in four leg specimens) were felt to have been completely released. The first evaluator considered that the deep posterior compartment was incompletely released in two specimens. The second evaluator considered that the superficial posterior compartment was incompletely released in two specimens. The only complication was a large laceration of the soleus muscle that occurred during a period of blurred video signal attributed to a drop in bandwidth. Conclusions: This study suggests that surgical telementoring may enable physicians to safely perform two-incision leg fasciotomy in remote environments. This could improve the chances of limb salvage when compartment syndrome occurs far from surgical care. We found interobserver variation in the assessment of compartment release, which should be considered in the design of future research protocols.